Sejarah pendidikan vernakular Cina zaman kolonial British di negeri Perak, 1900-1941 - Phun, Lee Lee (Tanjong Malim, 2020)
Sejarah pendidikan vernakular Cina zaman kolonial British di negeri Perak, 1900-1941 by Phun, Lee Lee